Informal carers' support needs, facilitators and barriers in the transitional care of older adults: A qualitative study - Jacqueline Allen; Michelle Lobchuk; Patricia M. Livingston; Natasha Layton; Alison M. Hutchinson (Wiley, 2022)
Abstract Introduction Inclusion of informal carers in transitional care is challenging because of fast throughput and service fragmentation. This study aimed to understand informal carers' needs during the care transitions of older adults from inpatient care to the community. Methods A qualitative exploratory design was used with mixed‐methods data collection. Seventeen semi‐structured telephone interviews were conducted with family carers; one focus group was conducted by videoconference with two family carers and three community‐based advocacy and aged care providers; and eight semi‐structured telephone interviews were undertaken with healthcare practitioners from rehabilitation services. Data were thematically analysed. Findings All carers described the main social challenge that they needed to address in transitional care as 'Needing to sustain family'. Carers reported their social needs across five solutions: 'Partnering with carers', 'Advocating for discharge', 'Accessing streamlined multidisciplinary care', 'Knowing how to care' and 'Accessing follow‐up care in the community'. Focus group participants endorsed the findings from the carer interviews and added the theme 'Putting responsibility back onto carers'. All healthcare practitioners described the main social challenge that they needed to address as 'Needing to engage carers'. They reported their social solutions in three themes: 'Communicating with carers', 'Planning with carers' and 'Educating carers'. Discussion Findings highlight the importance of reconstructing the meaning of transitional care and relevant outcomes to be inclusive of carers' experiences and their focus on sustaining family. Transitional care that includes carers should commence at the time of hospital admission of the older adult. Conclusions Future sustainable and high‐quality health services for older adults will require transitional care that includes carers and older adults and efficient use of inpatient and community care resources. Healthcare professionals will require education and skills in the provision of transitional care that includes carers. To meet carers' support needs, models of transitional care inclusive of carers and older adults should be developed, implemented and evaluated. Public Contribution This study was conducted with the guidance of a Carer Advisory Group comprising informal carers with experience of care transitions of older adults they support and community‐based organizations providing care and advocacy support to informal carers.